Fabrication and characterization of polymer nanocomposites membrane (Cu-MOF@CA/PES) for water treatment. Issue 6 (December 2022) - Gowriboy, N.; Kalaivizhi, R.; Kaleekkal, Noel Jacob; Ganesh, M.R.; Aswathy, K.A.
Abstract: In present work, the hydrophilic Cu-MOF was synthesized by solvothermal method and incorporated with a cellulose acetate (CA)/polyether sulfone (PES) polymer membrane casting solution using a phase inversion approach to create new mixed matrix membranes of nanocomposite membrane material (Cu-MOF@CA-PES). The physical and chemical characteristics of the prepared materials were examined using different analytical techniques such as, FT-IR, XRD, TGA, XPS, SEM, TEM, AFM, BET and contact angle analysis. The membrane performance was analyzed using pure water flux (PWF), Bovine sirup albumin (BSA) and Humic acid (HA) rejection. The maximum water flux was 28.5 L m −2 h −1 with an 85 % BSA rejection rate and a 79 % HA rejection rate respectively and the contact angle value reduced from 75.27° to 46.02° respectively confirming that the modified membrane material is hydrophilic nature. The presence of Cu-MOF membrane material also exhibited outstanding anti-bacterial properties against pseudomonas aeruginosa, E. coli, Enterococcus faecalis and Staphylococcus aureus for gram positive and gram negative. Graphical Abstract: ga1 Highlights: Metal organic framework (MOF) is being studied extensively for developments in hybrid membranes due to their binding and attractive interaction in polymers. Engineered MOFs are used as fillers in ultrafiltration (U-F) polymeric membrane materials, which are designed for long-term water treatment. Cu-MOF was synthesized by solvothermal method and incorporated with CA/PES polymer membrane casting solution using a phase inversion approach to create new mixed matrix membranes. The fabricated membrane maximum water flux was 28.5 L m -2 h -1 with an 85% BSA rejection rate and a 79% HA rejection rate respectively and also exhibited outstanding anti-bacterial properties against pseudomonas aeruginosa, E. coli, Enterococcus faecalis and Staphylococcus aureus for gram positive and gram negative.